Homocysteine induces ferroptosis in cardiomyocytes by disrupting β-catenin/GPX4 pathway - Yanping Lei; Rui Liu; Lewu Xu; Yue Zhao (PLoS ONE, 2025)
Background Homocysteine can cause damage to cardiomyocytes, but the exact mechanism underlying that injury is unknown. And, ferroptosis contributes to both the initiation and progression of cardiac diseases. This study aims to focus on homocysteine to investigate the involvement of β-catenin/GPX4 signaling in ferroptosis of cardiomyocytes. Methods In this study, C57BL/6 mice were utilized to establish an experimental model. Hyperhomocysteinemia was induced in the animal model by administering homocysteine at a concentration of 1.8 g/L in the drinking water. Model mice received the treatment of deferoxamine (DFO) and ferrostatin-1 (Fer-1) as therapeutic interventions. Western blot was utilized to detect β-catenin, FTH1, and GPX4. Lipid ROS, Fe2+, and GSH were detected by biochemical assays. In addition, β-catenin and GPX4 expression were assessed by immunostaining techniques. Cell viability was assessed using CCK-8 assay, and mitochondrial damage was examined by transmission electron microscopy. ChIP combining dual luciferase reporter gene assay was performed to analyze the interaction between β-catenin protein with the promoter of GPX4 gene. Results Homocysteine inhibited β-catenin activity and GPX4 expression, and promoted cardiomyocytes ferroptosis in vitro and in vivo. Overexpression of β-catenin promoted the expression of GPX4 and subsequently inhibited homocysteine-induced ferroptosis in cardiomyocytes. Further, results from the ChIP assay and dual-luciferase reporter assay indicated that GPX4 acted as a target gene of β-catenin. Conclusion Homocysteine induces ferroptosis in cardiomyocytes by disrupting β-catenin activity, subsequently downregulating its target gene, GPX4.